OUVIR, ESCREVER E FALAR: UMA PESQUISA-AÇÃO SOBRE A UTILIZAÇÃO DO RÁDIO NO ENSINO FUNDAMENTAL - Silva, André Luis Rosa e (2007)
This research aimed at studying the use of radio at school. It started based on questions about the possibility of using school-radio (which has been described along the paper) as an instrument and mean of learning; about its role in the student’s cultural formation as well as its educational possibilities. The theorical references were based on the follow authors: Assumpção, Belloni, Citelli, Ferraretto and Vygotsky. This research goal were show the radio as an instrument which connects the formal and informal culture; identify the teachers and students conceptions about radio uses at school. Show the acquisition ways and use of radio language; characterize the school-radio as mediation instrument in the process of the media acquisition. With an action-research character, the research was run in a public school, in Ponta Grossa city, Paraná state, Brazil, from February to November 2005. The complementary methodological procedures of the research consisted of questionnaires application, regular meetings, which took place not only at school, but also in the laboratory of radio-journalism, at State University of Ponta Grossa, the roduction of fanzines, radio guide lines and spots, and radio programs. At the end of the research, students’ conception about radio was close to the concept of radio as an instrument an mean, proper to be used at school. Along the research, two fanzies, eight radio spots and two complete radio programs were produced. We may conclude that the radio production is a mediation instrument to the media culture acquisition, ant therefore its inclusion at school is justified. The radio programs production, when oriented by teachers, not only instigates the student’s creative expression, but also introduces the media universe as part of cultural formation of the teenagers in school age.